FAKTOR-FAKTOR YANG MEMPENGARUHI LABA PERUSAHAAN DAN IMPLIKASINYA TERHADAP KEPUTUSAN MANAJERIAL DITINJAU DARI ANALISIS PERILAKU BIAYA : SYSTEMATIC LITERATURE REVIEW - Zhafirah Thalia Carissa; Hanin Muthi'ah Nurarfani; Siti Mei Rahmawati; Mona Asifa Syariah; Rifani Akbar Sulbahri (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2026)
Through a Systematic Literature Review (SLR) approach, this study examines the factors that influence company profits when viewed from the concept of cost behavior and its influence on managerial decisions. The study was carried out by examining a range of scientific articles through several systematic stages, including identification, screening, eligibility evaluation, and the selection of relevant studies. The study found that corporate profits are influenced by cost structure, activity level, sales volume, selling price, and operational efficiency. Cost behavior analysis serves as a basis for management in planning strategies to increase profits and maintain stable company performance.